1996
DOI: 10.1083/jcb.133.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Topology of sphingolipid galactosyltransferases in ER and Golgi: transbilayer movement of monohexosyl sphingolipids is required for higher glycosphingolipid biosynthesis.

Abstract: Abstract. Glucosylceramide (GlcCer) is synthesized at the cytosolic surface of the Golgi complex while enzymes acting in late steps of glycosphingolipid biosynthesis have their active centers in the Golgi lumen. However, the topology of the "early" galactose-transferring enzymes is largely unknown. We used shortchain ceramides with either a 2-hydroxy fatty acid (HFA) or a normal fatty acid (NFA) to determine the topology of the galactosyltransferases involved in the formation of HFA-and NFA-galactosylceramide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 68 publications
1
93
0
Order By: Relevance
“…The original view of GSL biosynthesis placed the GlcCer translocation step in the Golgi complex (10,49,50). This was confirmed by studies of Buton et al (12), who showed that spin-labeled GlcCer is able to flip across rat liver Golgi vesicles in an ATP-independent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…The original view of GSL biosynthesis placed the GlcCer translocation step in the Golgi complex (10,49,50). This was confirmed by studies of Buton et al (12), who showed that spin-labeled GlcCer is able to flip across rat liver Golgi vesicles in an ATP-independent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…After synthesis in the lumenal lea£et of the Golgi, an SM analog with two truncated chains and C 6 -NBD^SM were found to be restricted to the lumenal lea£et of the Golgi membrane [142,225,226,229], implying that SM could not translocate from the non-cytosolic to the cyto-solic lea£et. This has indeed been observed for spinlabeled and C 6 -NBD analogs of SM in numerous studies on erythrocytes (see [230]), while also the reported di¡erence in SM species between the outer and inner lea£ets of the erythrocyte membrane could support the virtual absence of SM £ip [64].…”
Section: Transbilayer Translocationmentioning
confidence: 99%
“…In experiments on isolated Golgi membranes, newly synthesized LacCer and more complex glycosphingolipids did not translocate to the cytosolic surface. The data suggest that an energy-independent GlcCer translocator is present in the Golgi membrane [153,164,229]. Studies on transport of short-chain analogs of GlcCer to the cell surface have demonstrated that the multidrug transporters that transport C 6 -NBD^SM, MDR1 P-glycoprotein and MRP1 translocate GlcCer analogs as well [74,147,247].…”
Section: Transbilayer Translocationmentioning
confidence: 99%
See 1 more Smart Citation
“…FAPP2 (four phosphate adaptor protein 2, Godi et al, 2004) has a domain with homology (36% identity, 56% similarity) to the cytosolic glycolipid transfer protein GLTP (Abe et al, 1982;Metz and Radin,ER lumen but having free access to the cytosolic surface of the ER (Burger et al, 1996), are likely substrates. The proteins should not have access to complex glycosphingolipids, which reside in the non-cytosolic leaflet of the Golgi and endocytotic membranes.…”
Section: Synthesis Of Higher Glycosphingolipids Is Also Regulated By mentioning
confidence: 99%